Carbon capture and utilization for sodium bicarbonate production assisted by solar thermal power. (1st October 2017) - Bonaventura, D.; Chacartegui, R.; Valverde, J.M.; Becerra, J.A.; Verda, V.
Highlights: A novel technology integration for carbon capture and utilization is proposed. It relies on carbon dioxide absorption using sodium carbonate. As product is obtained a valuable chemical product sodium bicarbonate. Carbon dioxide sorbent produced by trona decomposition in a fluidized bed reactor. Preliminary analyses show advanced performance and revenues from the process. Abstract: In this paper, a novel carbon capture and utilization process is proposed. It is based on using a fraction of the captured carbon dioxide to produce sodium bicarbonate, a widely used product in the chemical and food industries. The process couples the Dry Carbonate process for carbon dioxide capture with sodium bicarbonate production. Raw material is trona or sodium sesquicarbonate dehydrate, which is a relatively abundant mineral composed by approximately 46% sodium carbonate and 35% sodium bicarbonate by weight. In the process, trona is firstly converted into sodium carbonate in a fluidized bed reactor operated at 180–200 °C and 1 bar. Heat required in the fluidized bed reactor for decomposing trona can be supplied by renewable sources such as low/medium temperature solar energy or biomass. A fraction of the sodium carbonate generated is recirculated for carbon dioxide capture by means of the dry carbonate process. The rest is converted to sodium bicarbonate in a carbonating tower through the reaction with carbon dioxide and water. After separation of sodium bicarbonate and other salts from water, the sodium bicarbonate produced is suitable for direct sale. The use of renewable sources for supplying the energy required at the sorbent regenerator and for trona decomposition yields a near-zero carbon dioxide emissions global system. As case of study, carbon dioxide capture coupled to sodium bicarbonate production has been analysed for a 15 MWel coal fired power plant. Heat required in the carbon capture process penalizes the global system efficiency by a 10.2%, which is reduced just to the electricity parasitic consumption for solids transport and carbon dioxide compression (∼3%) if renewable energy sources are integrated. From an economic perspective, the penalty in electricity consumption is fully compensated by the new by-product sales. Taking into account the reduction of electricity sales and current prices of trona and sodium bicarbonate a return of investment is obtained in the range between 3 and 8.7 years with an internal rate of return over 12%. These values improve the current forecast of any other carbon capture and storage process up to date, which suggests a high interest of the proposed conceptual integration specially for regions where trona is widely available.